Residual effect of biochar and saw dust powder on carbon and total nitrogen contents in Yellow Latosol in Amazonia - Guimaraes, Rodrigo de S.; Padilha, Felipe J.; Cedano, Johnny C.; Damaceno, Joao B.; Gama, Romildo T.; Oliveira, Danielle M. de [UNESP]; Teixeira, Wenceslau G.; Falcao, Newton Paulo de S. (Brazilian Chemical Soc, 2017)
The biochar (BC) acts as a physical, chemical and biological conditioner, which added to increasing doses of saw dust powder (PS) can contribute to soil improvement. The objective of this work was to verify the residual effect of BC and PS on total carbon, organic carbon, total nitrogen and carbon and nitrogen in a dystrophic yellow latosol in the central Amazon. The experiment was carried out at the experimental station of the National Research Institute of the Amazon, Manaus-AM. A randomized block design (4 blocks) was used in factorial tests, In the first plot (0, 40, 80, 120 t ha(-1)) of BC, and in the second, 80, 120 t ha(-1)) of PS, totaling 16 treatments and 4 replicates with 64 experimental units. Were determined the total carbon (TC) and nitrogen (NT) contents by the dry-combustion method, organic carbon (CO) by the Walkey & Black method and the carbon and total nitrogen C/N. There was a significant effect at the 1% level of significance in the CT contents at the two depths (0-10 and 0-20 cm) as the BC doses increased, with a difference of more than 80% between the Dose 0 (17.86 g kg(-1)) and 120 (32.16 g kg(-1)). There was significant interaction at the 5% probability level between BC and PS in depth 10-20 cm, with the interaction of doses 80 BC and 40 PS presenting the best mean with 34.67 g kg(-1) C. There was no significant effect for BC and PS on CO and soil organic matter (OM) in no depth. The residual effect of BC provided a significant increase at the level of 5% in total nitrogen contents at depths 0-10 and 10-20 cm. There was an increase in the C/N ratio due to the doses of BC in the three depths of the soil studied.
Keywords: Soil organic matter; Yellow Latosol; Soil Conditioner